BUDDHIST CANONS ON EDUCATION FOR AUTHENTIC AND SUSTAINABLE EDUCATION TOWARDS MEETING 21st CENTURY GLOBAL CHALLENGES - SINGH, DR. ALKA (JETA (Journal of English Teaching and Applied Linguistic), 2025)
Buddhist culture and related principles offer valuable insights into education, highlighting mindfulness, critical thinking, and compassion as essential principles for addressing 21st-century global challenges. These principles are crucial for fostering authentic and sustainable learning, empowering learners to address complex challenges such as sustainability, social inequality, and technological disruption. Buddhist principles, including mindfulness, critical thinking, and compassion, can be integrated into educational approaches to promote sustainable learning. Mindfulness practices improve emotional regulation, focus, and cognitive function, while critical thinking encourages analytical reasoning, reflective thinking, and discerning thinking. Compassion fosters empathy, kindness, and concern for others' well-being. The present paper offers a note on it.